Kolonisasi Kewargaan Digital - Nuruddin Al Akbar (Department of Politics and Government Science Univer, 2026)
WENDY H. WONG. We, the Data: Human Rights in the Digital Age. Cambridge, MA: MIT Press, 2023. 352 pp. ISBN 9780262048576.